Cyber Notary: Between Notary Opportunities And Challenges In Facing The Era Of Digital Disruption 4.0 Towards 5.0 - Agung Aditya; Cahya Wulandari; Loso Loso (LAW FACULTY UNISSULA, 2022)
The position of Notary as a profession that cannot be separated from the development of existing technology. The wave of technology in the Industrial 4.0 and Society 5.0 era requires Notaries to be able to move quickly, especially in carrying out their duties. Major changes in technological developments have encouraged the Indonesian nation as a modern democracy to transform its electronic system for the public interest. The term Cyber Notary emerged in this case, which was discussed as being able to speed up the work of a Notary as a public servant in terms of making a Notary deed. If it is based on the values that shape it, technology and politics are of course different, technology thrives in scientific knowledge and objective facts while law is made in the public domain which demands technical regulation in the reciprocal relationship between culture, politics and technology. This is concretized by Act No. 14 of 2008 concerning Public Information Disclosure (UU KIP) and Act No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE) in conjunction with Act No. 19 of 2016.